Analisis Framing Robert Entman Pada Editorial Pemberitaan Pon Aceh Sumut 2024 di Media Indonesia.Com dan Kompas.Id - Adinda Mustika Sari; Indah Mawarni (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
National Sports Week (PON) is the biggest sporting event in Indonesia, which brings together the best athletes from all provinces. In 2024, it will be the 21st PON which will take place in Aceh and North Sumatra. This research aims to analyze the framing of the editorial reporting on the Aceh-North Sumatra National Sports Week (PON) from two national media, namely Media Indonesia.com and Kompas.id using Robert Entman's framing analysis model. This analysis was carried out to find out how the two media frame the issue, highlight certain aspects, and their impact on readers. Based on research, it was found that the two media have different approaches in framing the 2024 Aceh-North Sumatra PON.